PENGARUH CR, DER, TATO, DAN ROA TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER - Naili Fiqayati; Sri Mulyani; Ulva Rizky Mulyani (STIE Mahardhika, 2026)
This study aims to analyze the effect of internal financial indicators, namely Current Ratio, Debt to Equity Ratio, Total Asset Turnover, and Return on Assets, on profit growth. The population of this study consists of primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research adopts a quantitative approach. The sampling method used was purposive sampling, resulting in 34 companies as the sample and generating 170 research observations. The data were analyzed using panel data regression with the assistance of EViews 12 software, and the test results indicated that the Fixed Effect Model (FEM) was the most appropriate estimation model. The findings show that the Debt to Equity Ratio and Total Asset Turnover have a negative effect on profit growth, while the Current Ratio and Return on Assets have no effect on profit growth.